Please check and correct my work.
Logarithm solve for (x)
ln(x-3)+ln(x+4)=1
My Steps:
-Law 1: ln[(x-3)(x+4)]=1
-e^1=x^2+x-12...?

- anonymous

- schrodinger

See more answers at brainly.com

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions

- anonymous

couldn't you simply leave it in the expanded form and e both sides it would give you x=e-1/2

- anonymous

if you do it the way you were doing it you have to use the quadratic formula your steps are right

- anonymous

Okay now im a bit confused. could you show me how

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- anonymous

well e^ln(x-3)+e^ln(x+4)=e^1 which is x-3+x+4=e, 2x+1=e
solve for x

- anonymous

don't listen to calc2student he doesn't know what he is talking about, that is not a rule of logs aka e^(ln(x-3)+ln(x+4) =\ x-3+x+4

- anonymous

repeat you did it correct do not listen to calc2 student, x=(e-1)/2=0.859.... your method the right one x=-4.37, +3.37

- anonymous

please this is the second question you have answered incorrectly calc2student stop responding to questions if you don't know how to help

- vijay

x = 6.7 and 0.29

- vijay

if u need more help, i can explain

- anonymous

sigh.... (-b+-(b^2-4(a)(c))^1/2)/2 = (-1+-(1-(4*-14.72)^1/2)/2 = (-1+-7.74)/2 = -4.37 or +3.37 feel free to check my work if you need to oh btw x^2+x-12-2.71; a=1, b=1, c=-14.71

- anonymous

well i put it in and it says its wrong...

- vijay

can u make sure is that log or ln ?

- vijay

if it is log my answer is correct

- anonymous

ln(x-3)+ln(x+4)=1
...so its ln

- anonymous

it should just be 3.37 b/c you can't take the the natural log of a negative number, check wolfram alpha it concurs with me..... if you have never used www.wolframalpha.com I highly suggest you try it :)

- anonymous

can u help me with this one?

- anonymous

solve the equation. Round to nearest 4 decimal place if necessary
(x^2)(5^x)-(5^x)=0

- anonymous

1,-1

- anonymous

(x^2)(5^x)-(5^x)=0-->5^x(x^2-1)=0-->x^2-1=0-->x=+-(1)^(1/2)-->x=+1,-1

- anonymous

(x^2)(10^x)-(x)(10^x)=6(10^x)

- anonymous

and thanks for the steps, greatly appreciated and needed for me to study

- anonymous

same factor out the 10^x---> x^2-x=6--->x^2-x-6-->x=3,-2

- anonymous

i have this problem. but it has this weird sign after. i posted it on google documents so you could see it. I thought maybe it would affect the question is some way....heres the link: https://docs.google.com/document/d/1C3mBIu2pp2Q1LUPo4I-ABl6XFxG56PxOrmH6qFAnxJg/edit?hl=en&authkey=CIKk49gI ...if the link works

- anonymous

now your pushing my algebra skillz to the limit..... so it maybe 1/2 but I'm not sure sorry

- anonymous

or it could be 8.... lol sorry really I don't really know this one

- anonymous

lol.... no for real it could be 2.... this time I think its right :)

- vijay

ln(x-3)+ln(x+4)=1
lnx / ln 3 + lnx * ln4 = 1
ln(x) [1/ln3 + ln4]=1
ln(x)[1+ln3*ln4]=ln3
ln(x)= ln3/(1+ln(3)*ln(4)
= ln3(1+ln7)

- vijay

last line is = ln3 / (1+ln7)

- anonymous

was I wrong?

- anonymous

how about x=-0.7937

- vijay

x should be more than 3, because there is ln(x-3), ln will not take negative value

- anonymous

uuggghhh.... yeah we've deciphered that he posted a link to another problem.... and btw you were definitely wrong on your last response to that problem.... in fact I have no idea what you were doing @vijay

- anonymous

vijay, you have your log properties mixed up. ln(a) - ln(b) = ln(a / b), not the other way around.
Donovan, your original post was all correct. You should have:
(x - 3)(x + 4) = e
x^2 + x - 12 = e
x^2 + x = e + 12
x^2 + x + 1/4 = e + 12 + 1/4
(x + 1/2)^2 = e + 49/4
\[(x + 1/2)^2=(4e+49)/4\]
\[x + 1/2 = \pm \sqrt{4e+49}/2\]
\[x = (-1\pm \sqrt{4e+49})/2\]
Only the positive version is going to work, which is x = 3.369. The negative version results in a negative x which won't work.

- anonymous

yeah I posted that like days ago @branlegr check out the link he posted and tell me what you get

- anonymous

@branlegr I'm a huge fan of wolfram as well ;)

- anonymous

Haha, I just saw it. Got kinda mixed up in all this back-and-forth of incorrect methods.

- anonymous

And that problem at that link is a b****.

- anonymous

yea I'm thinking 2^(1/log3(x))=2^-2-->1/log3(x)=-2--->1=-2log3(x)-->-1/2=log3(x)--->x^3=-1/2--->x=(-1/2)^(1/3)=~-0.7937.... I really do think that one is correct but I'm not sure... oh well

- anonymous

Imma working on it...

- anonymous

Answer is 1/sqrt(3).
\[2^{1/\log_{3}x }=1/4\]
\[\ln 2^{1/\log_{3}x }=\ln 1/4\]
\[(1/\log_{3}x)\ln 2=\ln 1/4 \]
\[1/\log_{3} x=\ln(1/4)/\ln 2\]
\[1 /\log_{3}x=\log_{2}1/4 \]
\[1/\log_{3} x=-2\]
\[\log_{3} x=-1/2\]
\[3 ^{-1/2}=1/\sqrt{3}\]

- anonymous

nice I was totally wrong.... confused the last rule... bs lol back to organic II have a good night man sorry I couldn't help more :(

Looking for something else?

Not the answer you are looking for? Search for more explanations.